Dubhe: A Reliable and Low-Latency Data Dissemination Mechanism for VANETs - Lifeng Zhang; Beihong Jin (International Journal of Distributed Sensor Networks)
Many attractive applications over vehicular ad hoc networks (VANETs) need data to be transmitted to the remote destinations through multihop data forwarding, but some unique characteristics of VANETs (i.e., high node mobility, dynamic topology changes with frequent link breakage, and unstable quality of wireless transmission) incur unstable data delivery performance. In order to reliably and quickly disseminate the data, we present Dubhe which includes a delay model and an improved greedy broadcast algorithm embedded with a coverage elimination rule. The former is used for making decisions for path selection with the aim of minimizing the transmission latency, while the latter focuses on boosting the reliability of one-hop data transmission. We also analyze the necessity and effectiveness of Dubhe and the retransmission overheads theoretically. It is shown from the experiments that Dubhe can achieve high-reliability and low-latency data delivery in comparison with the epidemic-based protocol and the static-node-assisted adaptive data delivery protocol.